SUPERVISORY CONTROL (SCADA) SYSTEMS AND THEIR IMPLEMENTATION IN THE HIGH VOLTAGE PLANTS - CVEJIC Radoje; MARKOVIC Aca; CVEJIC Rosica (Annals of the Oradea University: Fascicle Management and Technological Engineering, 2014)
SCADA (Supervisory Control and Data Acquisition) systems (or SCADA networks) are software support for supervision and control of industrial processes. Today there are thousands of installed SCADA systems, which can be mutually completely different in terms of their structure, but at the same time have a common basic elements and basic purposes: Monitoring, Control and Data Acquisition. In the paper, in addition to basic information about SCADA systems, their function and elements, there will be presented their implementation in the high voltage 110 kV plant of the Thermal Power Plant of Kostolac A.